Performance assessment of PVSyst-based grid-connected solar systems in Gharraf City, Iraq - Rhaif, Raheem H (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Renewable energy is in high demand in many countries around the world because of the increased demand of energy and environmental issues associated with greenhouse gas emissions. Fossil fuels are still predominant in the USA but their sustainability in the long run cannot be truly guaranteed, which is why the transition to clean energy is necessary. The paper assesses the output of a 6 kW grid-tied photovoltaic (PV) system mounted in Iraq at Al-Gharraf City. The PVsyst software was used to perform the simulation to determine the annual energy generation, the system efficiency, and design optimization. The PV system proposed produces an annual energy of 9,192kWh with a yield of 1532 kWh/kWp/year. The average performance ratio of the calculated was 74.68% which means that the system can be operated reliably under the local climatic conditions. The essential novelty of the work is that it gives the indicators of real regional performances of small-scale grid-connected PV installations in southern Iraq, where not many evaluations have been documented so far. It is believed that the findings will be helpful in implementing solar energy in the future as well as assist in better technical planning of renewable energy projects in Iraq.